AN ANALYSIS OF MORAL VALUES IN LALALAND’S FILMATMAN V SUPERMAN MOVIE “DAWN OF JUSTICE” BY ZACK SYNDER - JUNIAR .; RIDWAN SYAHPUTRA (LP2MTBM MAKARIOZ, 2019)
This research is aimed at getting the result of moral value in Batman V Superman movie